Politeness strategies used by detectives in the movies murder on the Orient Express and Knives Out - Sazali, Muhammad Zuhairi Shah; S. Mohandas, Eliyas (Universiti Teknologi MARA, 2023)
Politeness strategies are known to be speech acts that express concern for others and minimise threats to face in social contexts. It is used not just in conversations but politeness strategies can also be used in written messages. Politeness strategies are important as they are used to maintain social order and its main use is to avoid conflicts. Politeness strategies are critical in verbal communications as impolite words and rude expressions which are used in communicating with other people would result in lack of cooperation and failure to obtain compliance particularly in negotiation. In this research, Brown and Levinson’s concept of Politeness Strategies was employed as the main framework to execute the study. This study investigated the subject movies, "Knives Out" and "Murder on The Orient Express” to recognize the different kinds of politeness strategies utilised by the detectives in the movies and examine the likenesses and contrasts of politeness strategies utilised by the two main characters in the subject movies, from two different cultural backgrounds; American and Belgian. A qualitative method design was utilised for this research. The screenplay from both movies was transcribed and the scripts with politeness strategies will be chosen and utilised for analysis. Information from the research is gathered and dissected using descriptive and qualitative analysis. Hercule Poirot has found to be the most dominant in Positive Politeness Strategies, opposing his counterpart in this study, which is Benoit Blanc, who has the highest percentage committing Off Record Strategies in his role in knives Out. The findings of the study are hoped to give a better insight into using politeness strategies in interactions, the importance of being polite in communication and how politeness can help improve communication in daily social engagements.